PENGARUH STRATEGI PEMBELAJARAN JOYFUL LEARNING BERBANTUAN PERMAINAN ROCQ TERHADAP MINAT DAN HASIL BELAJAR SISWA - Putri, Dwi Ditha; Enawaty, Eny; Sahputra, Rachmat (EduChem, 2023)
The purpose of this research is to determine the difference of student learning interest and students learning outcomes with the influence of joyful learning strategies with ROCQ (Ranking One Chemistry Quiz) game on the results of student learning outcomes. This study employed a Quasi-Experimental Design with "Nonequivalent Control Group Design". The sample was class X MIA 5 as control class and class X MIA 3 as experimental class. Based on the result of data analysis in this research, it can be concluded that there were many differences in students learning interest and student learning outcomes which was significant between experimental class with control class after using joyful learning strategies with ROCQ game. This can be finded which the result of U-Mann Whitney test   questionnaire interest in learning (Î± â‰¤ 0,05) was obtained sig (2-tailed) of 0,000 and posttest (Î± â‰¤ 0,05) was obtained sig (2-tailed) of 0,000. The effect of learning used joyful learning strategies with ROCQ game was 49,45% to increase in class X students learning outcomes in element periodic system material in SMA Negeri 1 Sungai Raya. So, it means by using joyful learning strategies can give the positive influence to the students interest and learning outcomes.Keyword : Joyful Learning Strategies with ROCQ Game, Learning Interest, Learning Outcome